DNA breakage induced by piceatannol and copper(II): Mechanism and anticancer properties - LI, ZHENSHENG (D.A. Spandidos, 2012)
Piceatannol (3,3′,4,5′-tetrahydroxy-trans-stilbene; Pice), found in a variety of plant sources including grapes, red wine, peanuts and rhubarb, is known as a metabolite and analog of Resveratrol (3,5,4′-trihydroxy-trans-stilbene; Res) and has higher bioactivity than Res. To explore the mechanism of DNA damage induced by Pice in the presence of copper (Cu)(II), gel electrophoresis, UV-visible spectroscopy, fluorescence spectroscopy and Fourier transform infrared spectroscopy were used. The results of gel electrophoresis demonstrated that the hydroxyl radical played a critical role in DNA cleavage. Spectroscopy confirmed that the mechanism of DNA cleavage induced by Pice-Cu(II) involves the Haber Weiss and Fenton reactions. Pice chelates with Cu(II) as a bidentate ligand, and the Pice-Cu(II) complex undergoes intramolecular electron transfer to form the semiquinone radical anion and Cu(I), which may be reoxidated by O(2) to form Cu(II) with hydroxyl radical generation. In brief, the formation of the hydroxyl radical and the Cu(II)/Cu(I) redox cycle play a key role in inducing DNA damage. In this process, Pice demonstrated pro-oxidant properties. Oxidative product(s) of Pice, semiquinone, was formed and Cu(I) was reoxidized to Cu(II). The redox cycling of copper generated reactive oxygen species, which induced DNA cleavage, the hallmark of cell apoptosis. The mechanism of DNA breakage induced by Pice-Cu(II) may be a significant pathway through which cancer cells are killed.